Selection and Neutral Mutations Drive Pervasive Mutability Losses in Long-Lived Anti-HIV B-Cell Lineages. (22nd February 2018) - Vieira, Marcos C; Zinder, Daniel; Cobey, Sarah
Abstract: High-affinity antibodies arise within weeks of infection from the evolution of B-cell receptors under selection to improve antigen recognition. This rapid adaptation is enabled by the distribution of highly mutable "hotspot" motifs in B-cell receptor genes. High mutability in antigen-binding regions (complementarity determining regions [CDRs]) creates variation in binding affinity, whereas low mutability in structurally important regions (framework regions [FRs]) may reduce the frequency of destabilizing mutations. During the response, loss of mutational hotspots and changes in their distribution across CDRs and FRs are predicted to compromise the adaptability of B-cell receptors, yet the contributions of different mechanisms to gains and losses of hotspots remain unclear. We reconstructed changes in anti-HIV B-cell receptor sequences and show that mutability losses were ∼56% more frequent than gains in both CDRs and FRs, with the higher relative mutability of CDRs maintained throughout the response. At least 21% of the total mutability loss was caused by synonymous mutations. However, nonsynonymous substitutions caused most (79%) of the mutability loss in CDRs. Because CDRs also show strong positive selection, this result suggests that selection for mutations that increase binding affinity contributed to loss of mutability in antigen-binding regions. Although recurrent adaptation to evolving viruses could indirectly select for high mutation rates, we found no evidence of indirect selection to increase or retain hotspots. Our results suggest mutability losses are intrinsic to both the neutral and adaptive evolution of B-cell populations and might constrain their adaptation to rapidly evolving pathogens such as HIV and influenza.